Diversities among Individuals with Cluttering - Arpana Bagachi; Rajasudhakar R (Journal of All India Institute of Speech and Hearing, 1970)
Cluttering is a disorder of speech and language processing, resulting in rapid, dysrhythmic, sporadic, unorganized and frequently unintelligible speech. Accurate prevalence figures are not known due to lack of adequate definitions and a significant proportion of clutterers do not seek treatment. Lack of academic training, lack of experience with clutterers and lack of published information are some of the reasons for not focussing on cluttering, a fluency disorder. The present study made an attempt to describe four clients who exhibited stuttering- cluttering symptoms by comparing their case file information. The study focused predominantly on the differential diagnosis of cluttering and other fluency disorders. Because cluttering is a syndrome, some of its identifying symptoms are shared by individuals with stuttering. In clutterers, the distinguishing traits include lack of awareness of communication difficulties, poor self monitoring of speech output, subtle impairment of language formulation problems and family incidence of similar communication problems. Also, the study illustrates the individual variability among individuals who clutter and their heterogeneous clinical manifestations. The possible overlap of between certain features of cluttering and stuttering were also discussed. To conclude that cluttering is a fluency disorder but not same as stuttering which can be getting hold of more systematic information on the nature and symptomatology of cluttering for identifying possible subtypes.